The Response of the Maine Food System to the Onset of COVID-19 Pandemic - Malacarne, JG; Lilley, Jason; McBrady, Nancy (Maine Policy Review, 2021)
The COVID-19 crisis had an immediate and extensive effect on food systems. Consumers suffered income shocks. Restaurants were forced to close. Wholesale markets for agricultural and seafood products disappeared. Retail food outlets had to balance increased demand, bottlenecks in their ability to resupply, and concerns for the health of their customers. Uncertainty about when these challenges would lessen contributed to the complexity of the decisions facing actors all throughout the system. The authors of this article bring together data from various sources to describe the response of the Maine food system to the onset of this crisis. Our descriptive analysis includes the actions, concerns, and adaptations of food producers, consumers, and vendors as they sought to weather and adapt to a challenging situation.
Keywords: Food consumers; food prices; food product availablity; food insecurity; local food sources; food producers; workforce; marketing channels